Barreiers and opportunities of the Republic of Moldova as a future member of the European Union - Stakhova, Nataliia; Zhyvko, Maksym; Petryshyn, Stanislav (Herald of Economics, 2023)
Introduction. The article explores the challenges and prospects faced by the Republic of Moldova in its ambitions to become a member of the European Union. Moldova’s geopolitical location, situated between EU member states and Ukraine, makes it a significant participant in the Eastern Partnership program. The main barriers hindering Moldova’s path to EU membership, such as political instability, corruption, and economic disparities, have been analyzed. The impact of the Transnistria conflict on the country’s European integration ambitions has also been studied. Potential opportunities and advantages Moldova possesses, such as commitments to democratic reforms and association agreements with the EU, have been examined. The continuous support from the EU towards Moldova’s European integration through financial assistance and cooperation in political matters has been highlighted. A roadmap for realizing Moldova’s European ambitions has been proposed, and the consequences of its potential future membership in the European Union have been revealed. Purpose. The aim of the article is to analyze the economic, political, and geopolitical issues influencing the Eurointegration processes in the Republic of Moldova, particularly its status as a candidate for European Union membership. Methods. To achieve the stated goal of the article, several specialized research methods were employed, including analysis and synthesis, induction and deduction, abstraction and concretization, systematization, and elements of comparative analysis. The methodological foundation for the research included national normative legal acts of the EU member states and the Republic of Moldova, as well as joint documents regulating integration processes. Additionally, scholarly works of domestic and foreign researchers, statistical reports, and other sources of information were utilized. This comprehensive approach facilitated a profound analysis and substantiation of conclusions regarding Moldova’s Eurointegration prospects and the necessity for implementing reforms to ensure successful membership in the European Union. Conclusions. The Republic of Moldova faces significant barriers, such as political instability, impeding the adoption of long-term reforms; widespread corruption affecting the business climate and investment potential; and economic disparities hindering regional development. Several promising opportunities for Moldova were identified during the research. These include commitments to democratic reforms and cooperation with the European Union. The conclusion was drawn that successful EU membership would grant Moldova substantial benefits, such as enhanced economic development, foreign investment attraction, access to the European market, and the promotion of contemporary standards across various sectors. The importance of implementing necessary reforms and changes to achieve Moldova’s Eurointegration goals and EU support in this process were emphasized. Discussion. The research findings indicate that the Republic of Moldova encounters internal and external barriers complicating its path to becoming a future member of the European Union. Political instability, corruption, and economic disparities remain significant obstacles to European integration. However, Moldova possesses the potential and opportunities for reforms and cooperation with the EU, increasing its chances of obtaining membership. EU support and commitment to democracy and European standards open doors to realizing potential advantages of EU membership. To succeed in Eurointegration processes, Moldova must continue implementing reforms and maintaining cooperation with the EU.